Hirudotherapy (medicinal leeches) for treatment of upper airway obstruction in a dog. Issue 5 (12th July 2021) - Trenholme, H. Nicole; Masseau, Isabelle; Reinero, Carol R.
Abstract: Objective: To describe upper airway obstruction (UAO) in a dog treated with medicinal leeches (hirudotherapy) as an ancillary therapy to hasten recovery. Case Summary: A 10‐month‐old neutered female Mastiff presented for acute respiratory distress. On admission, the dog was tachycardic, cyanotic, and orthopneic; stridor was audible. A 10‐cm soft tissue swelling in the right ventral cervical region and bruising around the rostral mandible were noted. At the time of endotracheal intubation, the trachea was deviated to the right as a consequence of severe soft tissue swelling that was contiguous with the sublingual hematoma and cervical region, causing loss of visualization of the arytenoids. A computed tomography with contrast scan of the head, neck, and thorax was performed, showing severe soft tissue swelling of the tongue, obliteration of the common pharyngeal/laryngeal regions from suspected hemorrhage, and rightward displacement of pharynx, larynx, and proximal trachea. Marked diffuse bronchial/bronchiolar thickening associated with bronchiolectasis and diffuse opacification of the pulmonary parenchyma with regions of consolidation were noted. The dog was minimally hypercoagulable on thromboelastography. The imaging results together with results of bronchoalveolar lavage cytology supported a comorbidity of eosinophilic bronchopneumopathy. Intubation was maintained with infusions of propofol and fentanyl, with minimal changes in oropharyngeal swelling within the first 18 hours of treatment. Medicinal leeches were then applied to the sublingual and cervical regions. There was continued slow bleeding from the sites of leech detachment, and the dog was able to be extubated at 44 hours, followed by hospital discharge. New/Unique Information Provided: Leeches are utilized in human medicine for treatment of UAO. Although UAO from hemorrhage has been described in dogs, this is the first report of medicinal leeches ( Hirudo verbana ) as complementary treatment for sublingual hematoma that contributed to UAO.